2005
DOI: 10.1016/j.msea.2004.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon content on the precipitation of secondary carbides and fatigue properties of a 5%Cr tempered martensitic steel

Abstract: In comparison with the conventional AISI H11 tool steel, which contains approximately 1 wt.% silicon, the modified steel AISI H11 (∼0.35 wt.% silicon) exhibits improved tensile and fatigue properties at 550 • C -the estimated tool surface temperature during the highpressure injection of aluminium alloys. The effect of silicon on the stability of secondary carbides was studied using transmission electron microscopy and small-angle neutron scattering. Silicon has a considerable influence on the precipitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 24 publications
8
70
0
3
Order By: Relevance
“…Considering the alloy elements were different in the two kinds hot work steels employed in this study, such as silicon, manganese, chromium, molybdenum and vanadium, Medvedeva 20) concluded that higher molybdenum content shows superior resistance to softening among the tested grades at all temperatures. Delagnesa 10) further pointed out that silicon inhibits the coarsening of the cementite and promotes its dissolution, carbon is available to form alloy carbides at lower tempering temperatures for the high silicon grade. As a consequence, the secondary hardening peak of the low silicon grade is shifted towards higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the alloy elements were different in the two kinds hot work steels employed in this study, such as silicon, manganese, chromium, molybdenum and vanadium, Medvedeva 20) concluded that higher molybdenum content shows superior resistance to softening among the tested grades at all temperatures. Delagnesa 10) further pointed out that silicon inhibits the coarsening of the cementite and promotes its dissolution, carbon is available to form alloy carbides at lower tempering temperatures for the high silicon grade. As a consequence, the secondary hardening peak of the low silicon grade is shifted towards higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease silicon content and increase molybdenum content can enhance the high temperature strength and thermal fatigue property, and several studies have suggested the benefit of it. 7,10) JIS SKD61 hot work steel is usually treated with thermochemical surface treatments such as nitriding, PVD and HVOF processes in order to increase service lifetime. 1115) Among these processes, nitro-carburizing treatment is regarded an effective, low cost method with many advantages, such as low treatment temperature, short treatment time, high degree of shape and high surface hardness due to the ¾-phase (Fe 23 N) and £A-phase (Fe 4 N) formed on the outmost surface.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a long term thermal load, there is the additional stress due to periodic change of the temperature [1]. Martensitic steels containing 5%Cr were originally developed for die casting of Aluminium alloys [5]. Other typical fields of applications include forging dies, mandrels, extrusion tools, pressure die-casting, and more.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is one of the main alloying elements and very effective in refining carbides by delaying the conversion of ε-carbide to cementite during tempering cycles [15]. It is reported that reduction in silicon content could increase the toughness of medium carbon quenched-tempered Cr-Mo alloy steels due to its ability in altering the nature and distribution of alloy carbides [16,17]. More recent work indicated that silicon can reduce the size of Nb-Ti carbides, precipitated in a cryogenic pressure vessel steels, and hence increased their ultra-low temperature toughness [18].…”
Section: Introductionmentioning
confidence: 99%